Exploring the Role of Social Media Marketing in Shaping Indonesian Tourists’ Interest and Perceptions of Turkey as a Travel Destination - Dharmawan, Winda Putri; GİRGİNER, Nuray (Journal of Indonesian Economic Research, 2025)
This study aims to explore the role of social media marketing in shaping Indonesian tourists’ interest in visiting Turkey. A qualitative approach was used, with data collected through in-depth interviews from 16 participants, including active social media users, Indonesian tourists who have visited or plan to visit Turkey, and travel agents in Indonesia. The results indicate that social media significantly influences travel decisions by providing engaging visual content, trustworthy user-generated reviews, and interactive promotions. Participants highlighted the emotional appeal of Turkey’s iconic landmarks and the influence of influencers in building trust. The study also found that while social media is more personalized and effective than traditional marketing methods, both should be used in combination for greater impact. The recommendations include optimizing visual content, collaborating with influencers, utilizing local language in campaigns, and strengthening engagement through interactive features to enhance social media marketing strategies.